Kinerja Kelompok Penyelenggara Pemungutan Suara Pemungutan Suara Ulang pada PEMILU 2019 di Kota Tebing Tinggi - Dian Husri Hurasan; Muryanto Amin; Hatta Ridho (Universitas Medan Area, 2022)
This research was motivated by the Re-Voting (PSU) and the Election Result Dispute (PHPU) lawsuit that colored the 2019 Election in Tebing Tinggi City. The performance of the Voting Organizer Group (KPPS) for the 2019 election in Tebing Tinggi City was questioned when the two problems initially stemmed from a mistake by KPPS at the polling station. To prove the performance of KPPS in Tebing Tinggi, the researcher analyzed the performance of KPPS in Kota Tebing Tinggi with 6 (six) indicators proposed by Robbins, namely: Quality, Quantity, Punctuality, Effectiveness, Independence, and work commitment. Because the performance of the organizers is part of the integrity of the election, the researcher uses the integrity theory of Frank and Martinez i Coma, which states that the performance of the organizing body can technically improve the integrity of the election and there is recognition of independence and Pippa Norris who examines the integrity of elections from the field of public management, namely examines electoral integrity using the concepts of electoral maladministration and 'good governance' which emphasizes technical capability and efficient performance, as well as electoral processes and procedures. This study found that although the Tebing Tinggi City KPPS has tried its best in carrying out its duties, the Tebing Tinggi City KPPS's performance is not good, this is due to several factors, namely: 1. Requirements regarding restrictions on serving as KPPS twice, 2. Minimal technical guidance and ineffective, 3. The logistical chaos of the 2019 election, 4. The complexity of the administration of the 2019 election, 5. The workload of the 2019 election that causes Human Error.